Evaluation of Antibacterial Activities of Some Medicinal Plants, Traditionally Used in Iran: Antibacterial activities of some medicinal plants - Mehrnaz Keyhanfar; Sonbol Nazeri; Maryam Bayat (Iranian Journal of Pharmaceutical Sciences, 2012)
The aim of this study was to assess the antibacterial activities of some medicinal plants extracts traditionally used in Iran. Hydroalcoholic extracts obtained from different parts of five plants including Rosmarinus officinalis L. (rosemary), Syzygium aromaticum L. (Clove)., Arctium lappa L. (Burdock) , Coriandrum sativum, Myrtus communis with traditional medicinal use were examined for their antibacterial activities against some gram-negative strains including Pseudomonas aeruginosa, Salmonella typhi, Proteus mirabilis, Klebsiella oxytoca and Shigella dysentriae. The disc diffusion method was applied to screen the antibacterial efficacy of the extracts. Gentamicin was used as control. This study showed that the extracts obtained from Syzygium aromaticum L., Arctium lappa L. and Myrtus communis had antibacterial activity against Proteus mirabilis. In addition, only the Myrtus communis extract had some inhibiting effect on the growth of Pseudomonas aeruginosa. The result of the current study revealed that some of the studied plants could be considered as potential source of antimicrobial agents and supports the traditional applications of a number of the tested plants as antibacterial reagents.